Examining Iranian Doctoral Students' Attitudes toward World Englishes - Behnaz Raji (Journal of English Language Studies, 2020)
This study investigated Iranian doctoral students' attitudes toward World Englishes (WEs). To meet the end of this study, 30 Iranian doctoral English students from Chamran and Islamic Azad Universities of Ahvaz, Iran were selected. Then, a Likert questionnaire with 20 items was administered to the participants. After answering the questionnaire, the collected data were analyzed by using One-Sample T-test. The results indicated that all the participants presented positive attitudes toward WEs and they considered WEs as valuable as SE. For example, participants stated that WEs can help us to communicate with all nations.